COVID -19: The Role of the Periodontologist (Nigerian Dental Journal, 2020)
COVID-19, since its outbreak in Wuhan, China has become a major public health phenomenon with the eventual declaration of a pandemic by the World Health Organization (WHO) in March 2020. The disease is considered to be transmitted through fomite and aerosol, therefore the concern for safety of both the dental teams and their patients. This review article seeks to report how the disease may possibly be transmitted within periodontal clinic and possible means of preventing such transmission. Internet search was done using words such as COVID-19, Dentistry, SARS-CoV-2, periodontal care, dental treatment, infection control and pandemic. Only articles written in English were accessed.
Keywords: COVID-19; SARS-CoV-2; Pandemic; Periodontology